Exclusionary Rules in China - Yi, Yan You (Columbia Journal of Asian Law, 2015)
This article conducts a close examination of China’s exclusionary rules, and presents a detailed discussion of its possible meanings as well as its advantages and shortcomings in the context of comparative law. Part I presents a general survey of China’s exclusionary rules, including the history of the relevant legislation, and ideas that furthered the legislation. Part II explores the relationship between the two provisions concerning excluding illegally obtained evidence and evaluating and examining evidence promulgated in 2010. Part III gives a detailed survey of the scope of China’s exclusionary rules, and introduces different interpretations of China’s criminal procedure rules. Part IV introduces rules concerning procedural issues of the exclusionary rules, and the burden of proof in relation to the legality of the obtainment of evidence. Part V summarizes the characteristics of China’s exclusionary rules in the context of a comparative analysis. The article argues that China’s exclusionary rules are mainly based on the concern of convicting innocent people, and this innocent people protection impetus makes the rules naturally weak in protecting all citizens in criminal procedure. Secondly, China’s exclusionary rules are based on the classification of evidence, and this classification results in many inconveniences, particularly when contrasted to the American rule that is based on the classification of rights. Thirdly, a discretionary exclusionary rule for physical and documentary evidence is not suitable for China. Fourthly, the absence of a poisonous tree doctrine may undermine China’s exclusionary rules in practice. Last but not least, China’s exclusionary rules may be classified as “judge-shared” exclusionary rules, contrasted to the American model of “judge-controlled” exclusionary rules.